2019
DOI: 10.3390/v11121106
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Calpains Can Cleave Structural Proteins from the Enterovirus Polyprotein

Abstract: Enteroviruses are small RNA viruses that cause diseases with various symptoms ranging from mild to severe. Enterovirus proteins are translated as a single polyprotein, which is cleaved by viral proteases to release capsid and nonstructural proteins. Here, we show that also cellular calpains have a potential role in the processing of the enteroviral polyprotein. Using purified calpains 1 and 2 in an in vitro assay, we show that addition of calpains leads to an increase in the release of VP1 and VP3 capsid prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(90 reference statements)
0
8
1
Order By: Relevance
“…An exciting development to inhibit protease activity has emerged from inhibiting the host cell calpain proteases. Calpain proteases are capable of proteolytically processing several target molecules, also including viral polyprotein that has been shown for enterovirus polyprotein [ 24 ]. Importantly, inhibitors against calpain proteases also efficiently inhibit the viral 3 C and M proteases [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An exciting development to inhibit protease activity has emerged from inhibiting the host cell calpain proteases. Calpain proteases are capable of proteolytically processing several target molecules, also including viral polyprotein that has been shown for enterovirus polyprotein [ 24 ]. Importantly, inhibitors against calpain proteases also efficiently inhibit the viral 3 C and M proteases [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory action was earlier suggested targeting early replication/translation of echovirus 1 as well as vesicle trafficking, necrosis, and apoptosis during Coxsackievirus B3 and B4 infection [ 55 , 56 , 65 ]. The molecular mechanisms of action were not detailed until recently, Laajala et al showed that calpain proteases can participate in the proteolytic processing of the viral polyprotein [ 24 ]. Thus, calpains could contribute to the same action as what is performed by the 3 C viral protease.…”
Section: Expert Opinionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the Rac1 protein described above, calpains 1 and 2 are not required for the entry of the virus, but rather at later stages of the infection in RNA replication [14]. It was recently demonstrated that cellular calpains can cleave viral capsid proteins VP1 and VP3 from the enterovirus polyprotein [23], and that enterovirus infection upregulates the activity of calpains, suggesting that calpains are essential for the cleavage of the viral polyprotein. Laajala et al [23] also demonstrated high cross-reactivity of calpain inhibitor 1 with the viral proteases 2Apro and 3Cpro, making it a promising antiviral drug.…”
Section: Introductionmentioning
confidence: 99%